Verification of good practices in food establishments in Petrolina, semi-arid region of Pernambuco, Brazil - Washington Luiz G. de Almeida Júnior; Jane Viana de Souza; Naiana Braga Freire; Francimaria Batista Miranda; Kênia de Fátima Carrijo; Francesca Silva Dias (Bioscience Journal, 2017)
This study was conducted jointly with the Municipal Sanitary Surveillance Agency of Petrolina, in the period of August-October 2013, to evaluate the hygienic-sanitary conditions of food producing and commercializing establishments in the municipality of Petrolina. A total of 300 food manufacturer/trader establishments were evaluated based on a Good Manufacturing Practices (GMP) checklist. The evaluation was based on 25 items. The data were computed as 0 for nonconformity and 1 for conformity to the GMP checklist. Data from all districts were analyzed by Principal Component Analysis (PCA). Items such as presence of lamp protectors, clean windows and screens, presence of SOP and training programs for handlers, use of aprons, caps, gloves and disposable towels, and performing periodic examinations of the establishments were evaluated. Fourteen evaluation items showed significant differences (P<0.05) for frequency of conforming and 9 for nonconforming. The PCA identified five city districts (Centro Norte, Areia Branca, Santa Luzia, Rio Corrente and São Gonçalo) in the municipality that used GMP in their establishments. These results highlight the need to redouble efforts in establishments to ensure the safety of products offered.